Pengembangan Asesmen Guru Biologi dalam Merancang Perangkat Pembelajaran Berbasis Kompetensi Pedagogik dan Profesional : (Development of assessment of biology teachers in designing learning tools based on pedagogic and professional competencies) - Meri Suryani; Bambang Hariyadi; Yusnaidar Yusnaidar (BIODIK, 2022)
This study aims to determine the development of the assessment instrument for biology teachers in designing learning tools based on pedagogic and professional competencies and the principal's perception of the assessment instruments that have been developed. The type of research used is instrument development research from the ADDIE model, this model has 5 stages, namely: analysis, design, development, implementation and evaluation. Instrument products before being tested are validated, product validation is carried out by material experts and design experts. Material expert validation got a score of 92% in the "Very Appropriate" category, so the assessment instrument was said to be feasible. Furthermore, the validation of the design experts got a score of 92% in the "Very Appropriate" category, then the practicality of the instrument resulted in 92% in the "Very Practical" category. This assessment instrument was tested one by one by researchers on three principals in Tebo Regency, namely SMA Negeri 3, SMA Negeri 10 and MAN 2. The results of the one-on-one trial were: (1) On each item in the assessment instrument that had been made the material or message conveyed or the purpose of using the assessment instrument is clear to the user. (2) The impact on users is that it can make it easier to make assessments of teachers, the items are specific. (3) The feasibility of using the product is in accordance with the available time. (4) The suitability of the items of the assessment instrument with the real world according to the user is appropriate. The field trial stage obtained an effectiveness of 92% with the "Very Effective" category. Based on the results of the study, it was concluded that the assessment instrument developed could be used by school principals on biology teachers in designing learning tools based on pedagogic and professional competencies. Key words: assessment instruments, teaching tools, pedagogic and professional competence, high school biology teacher AbstrakÂ  Penelitian ini bertujuan untuk mengetahui pengembangan instrumen asesmen guru biologi dalam merancang perangkat pembelajaran berbasis kompetensi pedagogik dan profesional dan persepsi kepala sekolah pada instrumen asesmen yang telah dikembangkan. Jenis penelitian yang digunakan adalah penelitian pengembangan instrumen dari model ADDIE, model ini terdapat 5 tahap yaitu: analysis, design, development, implementation dan evaluation. Produk instrumen sebelum diujicobakan terlebih dahulu divalidasi, validasi produk dilakukan oleh ahli materi dan ahli desain. Validasi ahli materi mendapatkan skor 92% kategori â€œSangat Sesuaiâ€, sehingga instrumen asesmen dikatakan layak. Selanjutnya validasi ahli desain mendapatkan skor 92% kategori â€œSangat Sesuaiâ€, kemudian praktikalitas instrumen dihasilkan sebesar 92% kategori â€œSangat Praktisâ€. Intrumen asesmen ini diuji coba satu-satu oleh peneliti pada tiga kepala sekolah di Kabupaten Tebo yaitu SMA Negeri 3, SMA Negeri 10 dan MAN 2. Hasil uji coba satu-satu yaitu : (1) Pada tiap butir di dalam instrumen asesmen yang telah dibuat materi atau pesan yang disampaikan atau tujuan dari penggunaan instrumen asesmen tersebut sudah jelas bagi pengguna. (2) Dampak bagi pengguna yakni dapat mempermudah dalam melakukan asesmen kepada guru, itemnya sudah spesifik. (3) Kelayakan penggunaan produk tersebut sudah sesuai dengan ketersediaan waktu yang ada (4) Kecocokan butir instrumen asesmen dengan dunia nyata menurut pengguna yaitu sesuai. Tahap uji coba lapangan diperoleh efektivitas sebesar 92% dengan kategori â€œSangat Efektifâ€. Berdasarkan hasil penelitian disimpulkan bahwa instrumen asesmen yang dikembangkan dapat digunakan oleh kepala sekolah terhadap guru biologi dalam merancang perangkat pembelajaran berbasis kompetensi pedagogic dan profesional. Kata kunci: Instrumen asesmen, perangkat mengacajar,Â  kompetensi pedagogik dan profesional, guru Biologi SMA